Tuberculosis among refugees and migrant populations: Systematic review. - Abyot Meaza; Habteyes Hailu Tola; Kirubel Eshetu; Tedla Mindaye; Girmay Medhin; Balako Gumi (PLoS ONE)
Tuberculosis (TB) is an important cause of morbidity and mortality among refugees and migrant populations. These groups are among the most vulnerable populations at increased risk of developing TB. However, there is no systematic review that attempts to summarize TB among refugees and migrant populations. This study aimed to summarize evidence on the magnitude of TB among refugees and migrant populations. The findings of this review will provide evidence to improve TB prevention and control policies in refugees and migrants in refugee camps and in migrant-hosting countries. A systematic search was done to retrieve the articles published from 2014 to 2021 in English language from electronic databases. Key searching terms were used in both free text and Medical Subject Heading (MeSH). Articles which had reported the magnitude of TB among refugees and migrant populations were included in the review. We assessed the risk of bias, and quality of the included studies with a modified version of the Newcastle-Ottawa Scale (NOS). Included studies which had reported incidence or prevalence data were eligible for data synthesis. The results were shown as summary tables. In the present review, more than 3 million refugees and migrants were screened for TB with the data collection period between 1991 and 2017 among the included studies. The incidence and prevalence of TB ranged from 19 to 754 cases per 100,000 population and 18.7 to 535 cases per 100,000 population respectively among the included studies. The current findings show that the most reported countries of origin in TB cases among refugees and migrants were from Asia and Africa; and the incidence and prevalence of TB among refugees and migrant populations is higher than in the host countries. This implies the need to implement and improve TB prevention and control in refugees and migrant populations globally. Trial registration: The protocol of this review was registered on PROSPERO (International prospective register of systematic reviews) with ID number, CRD42020157619.